P404 Persistence of subcutaneous infliximab after switching from intravenous in a French national cohort of IBD patients in remission. (30th January 2023) - Mathieu, N; Riviere, P; Heluwaert, F; Hébuterne, X; Chupin, A; Bouguen, G; Vuitton, L; Allez, M; Montuclard, C; Nachury, M; Nancey, S; Amélie, B; et al.
Abstract: Background: Subcutaneous infliximab (IFX-SC) was launched in France for the treatment of patients with inflammatory bowel disease (IBD) in 2021. Real-life and pharmacokinetic (PK) data after switching from intravenous infliximab (IFX-IV) to IFX-SC are needed. The PEREM study is a French multicenter prospective cohort aiming to describe the persistence of IFX-SC after switch from IFX-IV. Methods: IBD patients in steroid-free clinical remission [Harvey Bradshaw Index (HBI) ≤ 4 for Crohn's disease (CD) and partial Mayo score (PMS) ≤ 2 with each subscore ≤ 1 for UC] for at least 6 months on IFX-IV therapy were proposed to switch to IFX-SC as part of routine care. Patients were included in 40 centers between Oct 2021 and May 2022. Clinical scores (HBI, PMS), biological samples (CRP and fecal calprotectin - FC), PK and anti IFX antibodies (ATI) were evaluated 3, 6, 12 and 24 months after switch. In case of IFX-SC discontinuation, time and reason for withdrawal were documented. Safety and adverse events of interest were recorded. The primary endpoint was IFX-SC persistence at 12 months. As not all patients met this primary endpoint at the time of writing this abstract, we present here the results at 6 months (M6). Results: Among the 444 patients included [44% female, median age: 37 years (Min, Max: 18-88), 72% Crohn's], 71% were receiving IFX-IV at a dose of 5 mg/kg every 8 weeks and 84% were treated on monotherapy. Among the 417 patients analyzed, five withdrew their consent before the M6 visit and 324 were assessed at M6; 25/324 (7.7%) discontinued IFX-SC before M6 (seven for relapse, twelve for intolerance, two for pregnancy, four for unknown reasons) including one (0.3%) switch back to IFX-IV. Rate of survival without IFX-SC discontinuation at M6 was 92.6% (95% CI 89.3-95.1). Among the patients evaluated at M6, median clinical scores did not vary between inclusion and M6: HBI from 0 (IQR: 0-1) to 0 (IQR: 0-1), PMS from 0 (IQR: 0-0) to 0 (IQR: 0-0), respectively. The median CF and CRP levels were respectively 52 μg/g (IQR: 19-142) at inclusion and 37 μg/g (IQR: 14-129) at M6, and 1 mg/L (IQR: 1-4) at inclusion and 1 mg/L (IQR 0-4) at 6 months. At baseline, median infliximab levels were 6.6 μg/mL (min, max: 0-29) and 20 μg/mL (min, max: 0.3- 79.2) at M6. No major safety signals were recorded. Conclusion: In a national real-life multicenter cohort, rate of persistence of IFX-SC after 6 months was 92.6% in IBD patients switched in remission, without significant clinical or biological changes. Treatment switch was associated with an increase in IFX levels. These data are confirming the good efficacy and safety of IFX-SC after switch.